Intelligent Information Processing II
DOI: 10.1007/0-387-23152-8_8
|View full text |Cite
|
Sign up to set email alerts
|

Representing Human Spatial Behavior by Self-Organizing Networks

Abstract: Abstract:In this paper, we propose a way for mobile applications to recognize the daily spatial behavior of a user in the duration of a day. A feature representation of the user's spatial behavior is created from the accumulation of GPS location data logged in the user's everyday lives. By referencing this representationcalled "Behavior Map", mobile applications could infer a path the user will take, and behave proactively for locations where the user will be in.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In addition, it was demonstrated that the torsional response could be induced, even in a symmetric structure, owing to one‐directional ground excitation. Furthermore, it was confirmed that the proposed equations of motion [ 26 ] can predict the actual phenomenon well. When the Q – Δ resonance condition was satisfied, the translational acceleration response at the corner of the slab increased significantly.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In addition, it was demonstrated that the torsional response could be induced, even in a symmetric structure, owing to one‐directional ground excitation. Furthermore, it was confirmed that the proposed equations of motion [ 26 ] can predict the actual phenomenon well. When the Q – Δ resonance condition was satisfied, the translational acceleration response at the corner of the slab increased significantly.…”
Section: Discussionmentioning
confidence: 72%
“…Consequently, it is necessary to extensively investigate the Q – Δ effect. In a previous study, the authors conducted shaking table tests [ 26 ] and confirmed that the torsional response increased owing to the occurrence of the Q – Δ resonance. Moreover, it was considered that the occurrence of the Q – Δ resonance could be predicted using a theoretically deduced condition based on the considered equation of motion.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation